2012
DOI: 10.3349/ymj.2012.53.4.801
|View full text |Cite
|
Sign up to set email alerts
|

Existence of a Neuropathic Pain Component in Patients with Osteoarthritis of the Knee

Abstract: PurposePain from osteoarthritis (OA) is generally classified as nociceptive (inflammatory). Animal models of knee OA have shown that sensory nerve fibers innervating the knee are significantly damaged with destruction of subchondral bone junction, and induce neuropathic pain (NP). Our objective was to examine NP in the knees of OA patients using painDETECT (an NP questionnaire) and to evaluate the relationship between NP, pain intensity, and stage of OA.Materials and MethodsNinety-two knee OA patients were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
140
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(176 citation statements)
references
References 21 publications
(23 reference statements)
22
140
1
5
Order By: Relevance
“…However, since cartilage is both an avascular and aneural tissue, the mechanism of pain is likely to be complex and the synovium, bone and soft tissue probably contribute to pain generation. 4,5 In addition, subchondral bone pathology may cause neuropathy after destruction of the chondral structure, because the subchondral bone is densely innervated. 4 Rat models of knee OA have shown that sensory nerve fibers innervating the knee are significantly damaged with destruction of subchondral bone junction and induce neuropathic pain (NP).…”
mentioning
confidence: 99%
“…However, since cartilage is both an avascular and aneural tissue, the mechanism of pain is likely to be complex and the synovium, bone and soft tissue probably contribute to pain generation. 4,5 In addition, subchondral bone pathology may cause neuropathy after destruction of the chondral structure, because the subchondral bone is densely innervated. 4 Rat models of knee OA have shown that sensory nerve fibers innervating the knee are significantly damaged with destruction of subchondral bone junction and induce neuropathic pain (NP).…”
mentioning
confidence: 99%
“…Більше того, у частини пацієнтів больовий синдром не зменшується й після оперативних втручань, таких як ендопротезування суглоба [16]. Останні дані свідчать, що біль у хворих з ОА може включати як ноцицептивні, так і нейропатичні механізми [2,5,6,11,12,15]. Не-йропатичний біль (НБ) є результатом пошкодження нервів чи дисфункції соматосенсорної системи [10].…”
Section: âñòóïunclassified
“…Оскільки субхондральна кістка іннервується, її пато-логія може бути причиною нейропатичного болю піс-ля деструкції хондральної структури на пізніх стадіях ОА [11]. Джерелом нейропатичного болю можуть бути нервові волокна, ріст яких активується після пошко-дження структур суглоба.…”
Section: âñòóïunclassified
See 1 more Smart Citation
“…3 групи пацієнтів отри-мували лікування мелоксикамом, прегабаліном, ме-локсикамом і прегабаліном протягом 4 тижнів від-повідно. Результати досліджень виявили вірогідне зниження болю й скутості за шкалою WOMAC у гру-пі пацієнтів, які приймали мелоксикам і прегабалін, порівняно з іншими 2 групами [52,53].…”
Section: проблема номера / Problem Of This Issueunclassified